Fe-Vacancy-Ordered Fe4Se5: The Insulating Parent Phase of FeSe Superconductor - Yeh, Keng-Yu; Chen, Yan-Ruei; Lo, Tung-Sheng; Wu, Phillip M.; Wang, Ming-Jye; Chang-Liao, Kuei-Shu; Wu, Maw-Kuen (Frontiers in Physics, 2020)
We have carried out a detailed study to investigate the existence of an insulating parent phase for FeSe superconductor. The insulating Fe4Se5 with √5 × √5 Fe-vacancy order shows a 3D-Mott variable range hopping behavior with a Verwey-like electronic correlation at around 45 K. The application of the RTA process at 450 °C results in the destruction of Fe-vacancy order and induces more electron carriers by increasing the Fe3+ valence state. Superconductivity emerges with Tc 8K without changing the chemical stoichiometry of the sample after the RTA process by resulting in the addition of extra carriers in favor of superconductivity.